2009
DOI: 10.1093/mutage/gep027
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and morphological transformation induced by cobalt nanoparticles and cobalt chloride: an in vitro study in Balb/3T3 mouse fibroblasts

Abstract: Nanotechnology is an emerging field that involves the development, manufacture and measurement of materials and systems in the submicron to nanometer range. Its development is expected to have a large socio-economical impact in practically all fields of industrial activity. However, there is still a lack of information about the potential risks of manufactured nanoparticles for the environment and for human health. In this work, we studied the cytotoxicity, genotoxicity and morphological transforming activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 25 publications
3
100
0
Order By: Relevance
“…Based on the ICP-MS analysis of the stock suspensions, we did not observe the presence of metal impurities so their potential toxicity, which might influence the experiment outcome, was excluded. However, the cytotoxic effect of Ag NPs could be reasonably explained by the Trojan-horse mechanism, involving ion release by NPs inside the cell, as previously suggested for cobalt NPs that can easily release ions [20,42]. After 72 h of Balb3T3 cells exposure to Ag NPs, the IC50 values were: 1.7 µM (0.18 µg of Ag/mL) for Ag 44 nm, 1.9 µM (0.20 µg of Ag/mL) for Ag 84 nm, 3.2 µM (0.35 µg of Ag/mL) for Ag 100 nm and 1.5 µM (0.16 µg of Ag/mL) for NM-300, respectively.…”
Section: Nanoparticlesmentioning
confidence: 57%
See 2 more Smart Citations
“…Based on the ICP-MS analysis of the stock suspensions, we did not observe the presence of metal impurities so their potential toxicity, which might influence the experiment outcome, was excluded. However, the cytotoxic effect of Ag NPs could be reasonably explained by the Trojan-horse mechanism, involving ion release by NPs inside the cell, as previously suggested for cobalt NPs that can easily release ions [20,42]. After 72 h of Balb3T3 cells exposure to Ag NPs, the IC50 values were: 1.7 µM (0.18 µg of Ag/mL) for Ag 44 nm, 1.9 µM (0.20 µg of Ag/mL) for Ag 84 nm, 3.2 µM (0.35 µg of Ag/mL) for Ag 100 nm and 1.5 µM (0.16 µg of Ag/mL) for NM-300, respectively.…”
Section: Nanoparticlesmentioning
confidence: 57%
“…The same group has demonstrated that repeated doses of 42 nm uncoated Ag NPs were able to induce significant inflammation, involving increase of the cytokines produced, B cells distribution and tissue infiltration of inflammatory cells [16]. Distribution and accumulation of three different Ag NPs sizes (20,80 and 110 nm), administered by intravenous injection in rats once daily for 5 days, were found for the smallest Ag NPs (20 nm) in liver, kidneys and spleen, and for the larger Ag NPs (80 and 110 nm) in spleen, liver and lung [17]. The size-dependent distribution suggests those organ can be potential targets for Ag NPs in a size-dependent way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors assumed that Co 2+ ions, when released from cobalt oxide nanoparticles, are the primary source of toxicity through the induction of TNF--caspase-8-p38-caspase-3 in immune cells [70]. Co3O4 nanoparticles induced cytotoxicity, morphological transformation, and genotoxicity in Balb3T3 cells [71,72]. Co-nanoparticles induce genotoxic effects in human peripheral leukocytes [73].…”
Section: Cobalt Oxide (Co3o4) Nanocrystalsmentioning
confidence: 99%
“…In consideration that Co NPs can be internalized with a 50-to 100-fold increased uptake compared to cobalt chloride, resulting in the IC 50 value of 0.589-1.18 µg/mL (or 10-20 µM) for Balb/3T3 mouse fibroblasts, 15 our data indicate that Co NPs with nascent surface can significantly (almost 100-fold) decrease the cytotoxicity probably due to the exclusion of any contaminants, although the possibility that the bigger-sized Co NPs may not produce any cytotoxic effects as the case of Co NPs or that Balb/3T3 mouse fibroblasts may have higher sensitivity to Co NPs than the human cells used in our study cannot be ignored.…”
mentioning
confidence: 99%